Editor’s Note - González-Crespo, Rubén (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2020)
The research works presented in this issue are based on various topics of interest, among which are included: bayesian networks, evolutionary algorithms, virtual reality, web advertising, 3D technologies, traffic expression, Smart Cities, computational sustainability, computer vision, image recognition, deep neural networks, graphical models, mobile devices, human/complex system interactions, multi-agent systems, Physics inspired behaviours, etc.
Keywords: Editors Note; IJIMAI